The Role of Early Initiation of Breastfeeding for Successful Exclusive Breastfeeding among Working Mothers in Indonesia - Sumarmi, Sri; Laksono, Agung Dwi; Samsudin, Mohamad; Kusumawardani, Hastin Dyah; Rohmah, Nikmatur; Wisnuwardani, Ratih Wirapuspita (Nurse Media Journal of Nursing, 2026)
Background: Working mothers are often considered at risk for suboptimal exclusive breastfeeding (EBF) due to employment-related constraints. Early initiation of breastfeeding (EIBF) is widely recognized as a critical first step in optimal infant feeding; however, its specific contribution to sustained EBF among working mothers remains insufficiently quantified at the national level.Purpose: This study examined the role of EIBF in achieving EBF among working mothers in Indonesia.Methods: This secondary analysis used data from the 2022 Indonesian National Nutritional Status Survey, including 46,130 children aged 0−23 months born to working mothers. Exclusive breastfeeding was the outcome, with early initiation of breastfeeding as the main exposure. Seven covariates were examined: residence, maternal age, marital status, education, household wealth, antenatal care utilization, and child gender. Adjusted associations were estimated using binary logistic regression.Results: The prevalence of EBF among working mothers was 40.4%, while 59.7% practiced EIBF. Working mothers who initiated breastfeeding within the first hour after birth were significantly more likely to achieve EBF than those who did not (AOR = 1.715; 95% CI: 1.706−1.724). All covariates showed significant associations with EBF.Conclusion: EIBF emerged as the strongest determinant of EBF among working mothers in Indonesia, even after controlling for socioeconomic and health service factors. These findings provide robust national evidence supporting the integration of EIBF as a core strategy within maternal health services and workplace breastfeeding policies. However, maternal socioeconomic characteristics, health service utilization, and contextual factors also shape EBF practices, indicating the need for comprehensive multi-level strategies.